AIDS-related opportunistic infections in Hospital Kuala Lumpur. - Nissapatorn, V.; Lee, C.; Fatt, Q.K.; Abdullah, K.A. (Institute of Infectious Diseases, 2003)
We retrospectively reviewed 419 HIV/AIDS patients in Hospital Kuala Lumpur from 1994 to 2001. In the male group, the age range was 20-74, with a mean age 37 years, while in the female group it was 17-63, with a mean age of 33 years. With regard to age group, it was found that the preponderant age group was 25-34 years. The majority of male subjects were Chinese (52.5%), single (56.3%), and unemployed (55.1%), whereas the females were Malay (42.3%), married (79.5%), and non-laborer (64.1%). Also, both groups resided in Kuala Lumpur and had heterosexual contact as the leading cause of HIV transmission. More than half of the patients had CD4 cell counts of <200 cells/cumm. We found that the acquisition of HIV infection via intravenous drug use (IDU) was directly related to the incidence of tuberculosis infection (P < 0.05). Further analysis showed HIV-related tuberculosis with IDU was also dependently correlated with occupational status (unemployed) (P < 0.05). The four main AIDS-defining diseases include tuberculosis (48%), Pneumocystis carinii pneumonia (13%), toxoplasmic encephalitis (11%), and cryptococcal meningitis (7%); in addition, 53% of these patients were found to have CD4 cell counts of less than 200 cells/cumm at the time of diagnosis.